Flexibility-Flexicurity-Flexinsurance: Response to the European Commission's Green Paper "Modernising Labour Law to Meet the Challenges of the 21st Century" - Andranik Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2007)
The paper contains both critical remarks on and constructive suggestions to Green Paper: Modernising labour law to meet the challenges of the 21st century of the European Commission (2006a) which promotes flexicurity policies, that is, relaxing the employment protection legislation while providing advances in employment and social security for flexible workforces, like fixed-term, part-time and agency workers, or self-employed. The default assumption, that relaxing labour laws can be compensated by these advances, is criticised. These measures are regarded as too vague and insufficient, as also demonstrated in our previous study with empirical evidence. Therefore, some additional measures are proposed to counterbalance the actual flexibilization of employment relations, including (1) flexinsurance, a kind of progressive flexibilization tax, meaning that the employer's contribution to social security should be proportional to the flexibility of the contract/risk of becoming unemployed, (2) elements of the basic minimum income model, (3) constraining financial markets, as well as (4) developing adequate policy monitoring/evaluation instruments. It is argued that all of these meet interests of social partners and solve contradictions between such European policies as flexicurity, make work pay, welfare-state policy, and civil-society policy. Finally, we provide specific thoughts to 14 questions posed by the Green Paper.
Keywords: J65; J26; J21; J88; J83; 330; Flexicurity; labour market flexibility; social security; labour law; European employment strategy; Green Paper; Arbeitsmarktflexibilisierung; Sozialreform; Beschäftigungspolitik; EU-Politik; Kritik; EU-Staaten